Pengembangan Media Pembelajaran Berbasis Mobile Learning Melalui Game Edukasi Pada Materi Barisan dan Deret - Chakim, Muhammad Maulana Lukmanul; Kusumaningsih, Widya; Nugroho, Aryo Andri (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This development research aims to develop mobile learning-based learning media through educational games that are valid, effective, and can increase students' learning motivation. The type of research used is Research and Development (RND) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research was conducted at MAN Salatiga with class XI subjects. The data analysis techniques used in this study were a normality test, homogeneity test, right-hand t-test, two-sided t-test, and simple linearity test. The results of the study are a mobile learning-based learning media through educational games on the material of sequences and series stated: (1) It is suitable for use in learning activities based on expert validation. Media experts and material experts provide a very good feasibility assessment, (2) Effectively used as a learning medium by comparing the average learning outcomes, the experimental class is more prolific than the control class, (3) Can increase students' learning motivation with differences in learning motivation, class experimental class is better than the control class.